If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6k+2=3k+5k
We simplify the equation to the form, which is simple to understand
6k+2=3k+5k
We move all terms containing k to the left and all other terms to the right.
+6k-3k-5k=-2
We simplify left and right side of the equation.
-2k=-2
We divide both sides of the equation by -2 to get k.
k=1
| 10x^2+10x+3=19-4x^2+16 | | X-5+2x-4=12 | | 6.09x^2+4.57x-8.86=0 | | (7x-3)(2x+9)=0 | | 7(-6+3z)=42 | | x^3=79 | | 5t^2-10t-50=0 | | 27c+5-25c=49 | | 9a+5a+7a+8a= | | 5(4x-2)=2(3+6x) | | 15x-2x=-7x | | 42x-210=27x | | 3+10a-8=15 | | 6x-9+2x=5+8x-13 | | 2+x+y=x+5 | | 2x-2+2y=2+x+y | | 5r^2-19r-4= | | -3p+2+4p=-5 | | +65+(x-5)=180 | | x^4+15x-30= | | 7+20x=4(5x+3) | | 4y+9=3y-3 | | +65+(x-5)=60 | | 1.01*0.231= | | 6=-0.2r | | 5x+6=2x+13 | | 3x+2=3+x+3 | | 7y-14-4y+9=0 | | T=hp+b | | 3x+2=3+x-3 | | 3x+2=3+x-y | | 4x+7+5x=6x-11 |